Affinities of ribosomal protein S20 and C-terminal deletion mutants for 16S rRNA and S20 mRNA. - Donly, B C (1988)
We have measured the binding of E. coli ribosomal protein S20 and a number of C-terminal deletion mutants to 16S rRNA and in vitro transcribed S20 mRNA. Mutant S20s of interest were synthesized in vitro from the appropriate plasmid templates by coupled transcription and translation. The affinity of S20 produced in vitro for 16S rRNA is 1.2 x 10(7) (M-1) in a gel filtration assay. Removal of as few as 6 residues from the C terminus of S20 results in a sharp loss of binding activity, suggesting the presence of critical residues in this region. Analysis of the amino acid sequence of S20 indicates that these residues may constitute part of a segment of alpha helix. Although S20 is known to autoregulate its own synthesis, we were unable to demonstrate any measurable affinity of S20 for its own mRNA.